Monitoring of the Effectiveness of Public Relations to Optimize the Website of the Ministry of the Russian Federation for Affairs for Civil Defence, Emergencies and Elimination of Consequences of Natural Disasters - Zhdanova, O. S.; Deeva, I. V.; Skrynnikova, I. A.; Kadukova, R. R.; Leonova, D. V. (International Journal of Economics and Financial Issues, 2016)
Development of websites as an important component of PR-collaboration to achieve their audiences in today's information environment has become one of the defining criteria of perception of the effectiveness of state institutions activities. The study presents the initiation of market research to identify advantageous features, tools, and internet communication technologies in the activities of the five public institutions of Rostov region. Data analysis served as the justification for proposals of the expert group on benchmarking for the website of the Southern Regional Center of the Ministry of the Russian Federation for Civil Defense, Emergencies and Elimination of Consequences of Natural Disasters (SRC MES of Russia). Keywords: expert survey method, website optimization, online communications, public relations JEL Classifications: A10, 010, Z19